2015
DOI: 10.1097/pec.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Can Computerized Neuropsychological Testing in the Emergency Department Predict Recovery for Young Athletes With Concussions?

Abstract: Computerized neurocognitive testing in the ED has limited usefulness in predicting protracted symptoms. Total acute symptom burden may be a useful prognostic tool in the ED evaluation of concussed young athletes, yet further research is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
“…No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune system is an immune monitor and has a very report linking maternal child hood trauma-exposure with placental-fetal stress physiology, thus identifying a potential novel biological pathway of intergenerational transmission that may operate as early as during intrauterine life [7]. Blunt childhood renal trauma with pre-existing renal abnormalities was reviewed [8]. The retroperitoneal location affords the kidneys some protection from the forces experienced in blunt abdominal trauma, however the kidneys are at greater risk of injury when a disease process exposes them from their normal shielded location [8].…”
Section: Traumamentioning
confidence: 99%
“…Blunt childhood renal trauma with pre-existing renal abnormalities was reviewed [8]. The retroperitoneal location affords the kidneys some protection from the forces experienced in blunt abdominal trauma, however the kidneys are at greater risk of injury when a disease process exposes them from their normal shielded location [8]. The injuries may appear to be disproportionate in relation to the severity of the trauma history, confusing the imaging findings, and recognition of both the underlying disease process as well as the manifestations of acute trauma is important [8].…”
Section: Traumamentioning
confidence: 99%